LabOSat-01: a payload for in-orbit device characterization - Sanca, Gabriel Andrés; Barella, M.; Gomez Marlasca, Fernando; Alvarez, N.; Levy, Pablo Eduardo; Golmar, Federico (Institute of Electrical and Electronics Engineers, 2023)
Fil: Sanca, Gabriel Andrés. Universidad Nacional de San Martín. Escuela de Ciencia y Tecnología; Argentina